Factors associated with the patency loss of arteriovenous fistula for hemodialysis - Zlatko Maksimović; Nebojša Tasić; Siniša Maksimović; Nikola Gavrić (Biomedicinska istraživanja, 2018)
Introduction. The aim of the study is to examine the frequence of both early and later postoperative complications of arteriovenous fistula (AVF), as well as to determine the factors associated with the patency loss of AVF. Methods. The examination included 250 patients underwent native lower-arm AVF for hemodialysis createion, after which they had been monitored for at least six months. The patients were divided into two groups: group 1, consisting of 50 patients (30 males, aged 65.9 ± 11.9 years), in which there was the patency loss of AVF after 31.8 ± 38.8 months; group 2, consisted of 200 patients (106 males, aged 67.6 ± 9.5 years) with functional AVF that was followed for 57.5 ± 40.1 months. Apart from clinical state and AVF functionality, the biochemical parameters recommended for the hemodialysis patients were regularly checked. Results. There was significantly greater percentage of diabetes (42% vs. 12%), hypertension (42% vs. 2%) and anaemia (100% vs. 83.5%) found among the patients belonging to the first group, in comparison with the second one. On the other hand, there was no significant difference in the demographic, clinical and laboratory parameters. The patients from the first group had a significantly smaller diameter of the vein used for AVF (2.4 ± 0.25 mm vs. 2.7 ± 0.31 mm; p = 0.0001), frequently thickened venous walls (32% vs. 8%), as well as the lower quality of the artery used for AVF, in comparison with the second group. Time passed from the operation of AVF to its exploitation was significantly shorter in patients with than in those without occlusion of AVF (28.9 ± 6.6 days vs. 95.0 ±1 52.6 days; p=0.0025). The number of intraoperative, as well as early and later postoperative complications was significantly larger in the first group than in the second one. Hypotension, the use of AVF for hemodialysis less than 45 days after the creation, number of intraoperative complications, diabetes, anaemia, the previous cannnulation of the vein used for AVF, quality of artery and vein and the number of postoperative complications were selected by multivariate logistic regression analysis as independent factors associated with the patency loss of AVF. Conclusion. The patients with the patency loss of AVF had a significantly greater number of both intraoperative and postoperative complications. The patency loss of AVF is associated with the range of changeable risk factors the recognition and elimination of which can improve the AVF functionality status, as well as prolong the time of its exploitation.